Effectiveness of accelerated diagnostic protocols for reducing emergency department length of stay in patients presenting with chest pain: A systematic review and meta-analysis. - Jesse Hill; Nana Owusu M Essel; Esther H Yang; Liz Dennett; Brian H Rowe (PLoS ONE)
In recent years, there has been an increase in the use of accelerated diagnostic protocols (ADPs) and high-sensitivity troponin assays (hsTn) for the assessment of chest pain in emergency departments (EDs). This study aimed to quantitatively summarize the operational and clinical outcomes of ADPs implemented for patients with suspected cardiac chest pain. To be considered eligible for inclusion, studies must have implemented some form of ADP within the ED for evaluating adult (age ≥18 years) patients presenting with chest pain using Tn assays. The primary outcome was ED length of stay (LOS). Secondary outcomes included the proportion of patients admitted and the proportion with 30-day major adverse cardiac events (MACE). Thirty-seven articles involving 404,566 patients met the inclusion criteria, including five randomized controlled trials (RCTs) and 32 observational studies. A significant reduction in total ED LOS was reported in 22 observational studies and four RCTs. Emergency departments with longer baseline ED LOS showed significantly larger reductions in LOS after ADP implementation. This observed association persisted after adjusting for both the change in serial Tn measurement interval and transition from conventional Tn assay to an hsTn assay (β = -0.26; 95% CI, -0.43 to -0.10). Three studies reported an increase in the proportion of patients admitted after introducing an ADP, one of which was significant while 15 studies reported a significant decrease in admission proportion. There was moderate heterogeneity among the 13 studies that reported MACE proportions, with a non-significant pooled risk ratio of 0.95 (95% CI, 0.86-1.04). Implementation of ADPs for chest pain presentations decreases ED LOS, most noticeably within sites with a high baseline LOS; this decreased LOS is seen even in the absence of any change in troponin assay type. The decrease in LOS occurred alongside reductions in hospital admissions, while not increasing MACE. The observed benefits translated across multiple countries and health regions.